Concept of creating an e-Filing system of language innovations (media and ecological aspect) - Сизонов, Дмитро Юрійович (Logos-D.M. Stančienė, 2021)
The article analyzes language innovations that function in mass media communication. These innovations represent the information space of Ukraine from the point of view of media ecology and ecolinguistics. The proposed concept of creating an e-filing system of language innovations, will present these innovations on the web portal by several functional characteristics: the sphere from which the innovation entered the mass consciousness, the genre in which media innovation functioned for the first time, the psycholinguistic marker (Shevchenko, Syzonov 2019), the time of appearance of a new unit and derived innovations, extralingual factors. as a result, this will allow us to talk about the continuous updating of the lexical and phraseological fund of the Ukrainian language in the media, which proves the dynamics of modern language processes. The proposed research from the point of view of media ecology is innovative for Ukrainian linguistics, and therefore requires a wide field for discussion on the part of modern specialists based on innovative ideas of an interdisciplinary nature.
Keywords: language innovations; mass media communication; e-filing system; media linguistics